2016
DOI: 10.1097/mpg.0000000000001264
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Difficile Infection in Children

Abstract: Clostridium difficile is a sporogenic, anaerobic, Gram-positive, emerging enteric pathogen. It represents the most common cause of health care-associated diarrhoea in the United States, with significantly associated morbidity, mortality, and health care costs. Historically regarded as a little more than an innocent coloniser bystander of the gastrointestinal tract of children, C difficile has increasingly demonstrated its behaviour as a true pathogen in the paediatric age groups. This organism may be responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 91 publications
3
69
0
1
Order By: Relevance
“…The American Academy of Pediatrics (AAP) Committee, recommended avoiding routine testing for C. difficile in children younger than 1 year of age based on the known high rates of colonization and infrequent disease. They also recommended that testing should be limited in this age group to those with risk factors, as Hirschsprung disease or other severe motility disorders or in an outbreak situation [33]. Recent data have shown that 26% of pediatric disease that was treated due to CDI occurred in infants younger than one year of age and 5% occurred in neonates [7].…”
Section: Risk Factors Of CDImentioning
confidence: 99%
“…The American Academy of Pediatrics (AAP) Committee, recommended avoiding routine testing for C. difficile in children younger than 1 year of age based on the known high rates of colonization and infrequent disease. They also recommended that testing should be limited in this age group to those with risk factors, as Hirschsprung disease or other severe motility disorders or in an outbreak situation [33]. Recent data have shown that 26% of pediatric disease that was treated due to CDI occurred in infants younger than one year of age and 5% occurred in neonates [7].…”
Section: Risk Factors Of CDImentioning
confidence: 99%
“…Immunotherapy with monoclonal antibodies against CD toxin has also shown positive results in adults [19]. Very rarely, colectomy is used as a treatment for the complicated and life-threatening cases of CDI [7].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for recurrence of CDI in children include recent hospitalization, malignancy, and recent surgery, the use of the acid blocking and immunosuppressant agents and antibiotic use [7,13]. Recurrent CDI can also be treated with supportive care and pharmacotherapy such as metronidazole and vancomycin [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations